Crime Murder Investigation Process of Infant in Order by Biological Mother on Child Protection in Polres Purworejo Jurisdiction (Case Study in Polsek Butuh Purworejo) - Yuliantoro Yuliantoro; Akhmad Khisni (Jurnal Daulat Hukum, 2018)
The aim in this study were 1) to determine analyze the process of investigation of criminal infanticide by the biological mother in Polsek Butuh Purworejo; 2) to assess and analyze the process of investigation of criminal infanticide by the biological mother can provide protection for children; and 3) to study and analyze the obstacles encountered in the process of criminal investigation of infanticide by the biological mother. The method used in this research is empirical juridical approach or in other words the socio-juridical. Specifications of this research is descriptive. Data used in this study are primary and secondary data. The collection of data used in this research is to study literature and interviews. Analysis of the data used in this study is qualitative. In this study thatcriminal investigation process by the biological mother infanticide in Purworejo district police Butuh a police station covering the investigator, attack, inspection, and final completion and submission of the case file. The process of criminal investigation of infanticide by the biological mother can provide protection for children, in addition to whether or not made his case investigation conducted by the police of all elements also determine the chapter to be used against the offender. Investigators in the case of infanticide ensnared by the biological mother can use Article 80 paragraph (3), (4) by Act No. 35 Of 2014 on Amendment Act No. 23 of 2002 on the Protection of the Child, Article 338 of the Criminal Code. In the process of investigation of criminal offenses committed infanticide by the biological mother still there are issues both internally and externally, namely the ability of investigators that witnesses are hard to find at the scene.Keywords: Investigation; Crime; Killing Infant; Child Protection.